Complications Requiring Cochlear Reimplantation - Hajar Bahrani fard; Seied Basir Hashemi (Iranian Journal of Otorhinolaryngology, 2011)
Introduction: Otalgia is one of the complaints which may occur at any age. The etiology of the pain may be in the ear, structures around the ear or other head and neck structures. This is caused by the complex nervous connections in the head and neck areas, the ear, the pharynx and the nose. Since understanding the etiologies of referred otalgia can help in the assessment and treatment of the disease, this research was conducted to identify the etiologies of referred otalgia in patients visiting the ENT Clinic in Gorgan, Iran.   Materials and Methods: This prospective research was conducted on patients who visited the ENT Clinic with an earache, but in initial assessments the ear was normal. Patients’ data consisting of sex, age, complaint, the inflicted side, physical findings in the ear, the nose, the throat and head and neck were recorded in a questionnaire. These data were then analyzed with SPSS software.   Results: Of 770 patients with otalgia, 94 patients (12.2%) had referred otalgia. Of these patients 27.7% were men and 72.3% were women. The most common etiology of referred otalgia was dental problems (62.8%), and one patient who was being treated for pharyngitis had carcinoma of the base of the tongue. In 47.8% of cases the pain was in the left ear, in 43.4% in the right ear, and in 8.7% it was bilateral.   Conclusion:  In view of the fact that a significant proportion of the patients who complained of otalgia had no pathologies in the ear, thorough physical examination in adjacent structures especially teeth should be performed and malignancies should be considered as a possible etiology of otalgia.